Prevalence of sexually transmitted infections in symptomatic women of reproductive age group in a tertiary care centre - Verma, Aruna; Sirohi, Payal; Garg, Amit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Sexually transmitted infections (STIs) remain a significant global health challenge, affecting millions of individuals daily. This study aimed to investigate the prevalence and causative organisms of common STIs in women aged 18-49 years who presented with symptomatic vaginal discharge at a tertiary care hospital in India. The primary objective was to assess the prevalence of common STIs, including syphilis, gonorrhoea, chlamydia, trichomoniasis, human immunodeficiency virus (HIV), and candidiasis, through the use of specific diagnostic tests. Methods: A total of 100 non-pregnant women aged 18-49 years with vaginal discharge (excluding physiological discharge) were enrolled in the study. The research was conducted in the Department of Obstetrics and Gynecology LLRM Medical College, Meerut. Each participant was subjected to a detailed medical history and clinical examination. Vaginal and cervical swabs were taken for laboratory testing, and specific tests were performed for the detection of syphilis, gonorrhea, chlamydia, trichomoniasis, HIV, and candida. Data were analyzed using Microsoft Excel and statistical software such as GraphPad Prism 8.4.2 and statistical package for the social sciences (SPSS) version 25. Results: The study found that 15% of participants were diagnosed with an STI, with Candida infection being the most prevalent, affecting 66.67% of those with STIs. Chlamydia and Trichomonas infections each accounted for 13.33% of the cases, while one case of syphilis was reported. Significant correlations were observed between the type of vaginal discharge and the presence of STIs, with blood-stained and mucopurulent discharge being more common among STI-positive women. Conclusions: The prevalence of STIs observed in this study was consistent with findings in the broader epidemiological literature. Candida infection was the most frequently diagnosed, underscoring the need for targeted interventions, early detection, and awareness among women of reproductive age in both urban and rural settings.